Alteration of platelet glucose transport system in atherosclerosis - (:unkn) unknown (My University, 1986)
Functional and biochemical alterations of platelets in patients suffering from atherosclerosis were studied in our laboratory. One of the most striking alterations observed is in the platelet active glucose transport system. The Na+/K+ gradient dependent active transport system of glucose is found to be absent in the platelets of atherosclerotics. The platelet glucose transport kinetics in these subjects give unsaturable and linear kinetics. Furthermore, the specific glucose binding protein activity detected in the incubation fluid after cold osmotic shock to the platelets of normal subjects is found to be absent in the platelets of atherosclerotics. The platelet active glucose transport system is normal in juvenile onset diabetics, whereas it is impaired in maturity onset diabetics with clinical manifest atherosclerosis. The release inducers like ADP, adrenalin and collagen exert no effect on the platelet active glucose transport system. The specific glucose-binding protein is an unreleasable protein in the platelets of normal subjects. Hence, the absence of active glucose transport system in atherosclerotics is not due to the activated platelets in circulation.